DYNAMIC SYSTEM MODEL OF RICE COMMODITY AVAILABILITY FOR INCREASING THE NEEDS OF THE SOCIETY OF BALIKPAPAN CITY - Hertadi, Christopher Davito Prabandewa; Abdallah, Bayu Nur; Jayanti, Sekar Dwi (Journal of Industrial Engineering Management, 2024)
The availability of rice is a matter of considerable concern; this is related to food needs in an area, one of which is the City of Balikpapan. The city of Balikpapan is a city that has the potential to experience an increase in population due to increased birth rates and immigration and is supported by the discourse on the isolation of the National Capital. In one year, humans are able to spend 0.1146 tons/year. With an increase in population, it has the potential to increase rice consumption in the City of Balikpapan. Therefore, a rice availability simulation is carried out by considering the availability factors by using a Causal Loop Diagram and calculating factor values by using a Stock and Flow Diagram to see what conditions will be in the future after modeling. From the simulation, two scenarios were obtained to overcome the problem of rice availability in Balikpapan City, which resulted in an increase in the procurement and procurement of rice from Bulog and distributors, and the scenario chosen was scenario 2, namely an increase in rice procurement and distribution.